2015
DOI: 10.1097/id.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Behavior of Primary Human Osteoblasts Onto Microrough Titanium Surface

Abstract: Results indicate that the test group surface is more biocompatible, well tolerated, and suitable for supporting osteoblasts growth and proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…For this reason the rough sandblasted surface was treated by organic or inorganic acid etching which smoothened the peaks created by the formation of microcavities, and promoted protein adhesion which is essential for the early stages of bone healing 30) . It was already reported, in a previous study from our laboratory, performed on the same titanium discs, that the inorganic ions surface coating after acid etching surface was found to be more biocompatible and better tolerated by human osteoblasts 9) . A morphological study of the titanium discs, performed by AFM, reported in our previous work 9) , evidences a nanometric modification of the surface.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…For this reason the rough sandblasted surface was treated by organic or inorganic acid etching which smoothened the peaks created by the formation of microcavities, and promoted protein adhesion which is essential for the early stages of bone healing 30) . It was already reported, in a previous study from our laboratory, performed on the same titanium discs, that the inorganic ions surface coating after acid etching surface was found to be more biocompatible and better tolerated by human osteoblasts 9) . A morphological study of the titanium discs, performed by AFM, reported in our previous work 9) , evidences a nanometric modification of the surface.…”
Section: Discussionmentioning
confidence: 56%
“…It was already reported, in a previous study from our laboratory, performed on the same titanium discs, that the inorganic ions surface coating after acid etching surface was found to be more biocompatible and better tolerated by human osteoblasts 9) . A morphological study of the titanium discs, performed by AFM, reported in our previous work 9) , evidences a nanometric modification of the surface. The innovation of this surface is represented by the surface treatment which create a stable layer on titanium discs able to better promote cell adhesion, as firstly demonstrated by Zizzari et al 9) ,and subsequently by Gehrke et al 24) .…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations